3D Culture System for Liver Tissue Mimicking Hepatic Plates for Improvement of Human Hepatocyte (C3A) Function and Polarity. (4th March 2020) - Jia, Zhidong; Cheng, Yuan; Jiang, Xinan; Zhang, Chengyan; Wang, Gaoshang; Xu, Jiecheng; Li, Yang; Peng, Qing; Gao, Yi
Abstract : In vitro 3D hepatocyte culture constitutes a core aspect of liver tissue engineering. However, conventional 3D cultures are unable to maintain hepatocyte polarity, functional phenotype, or viability. Here, we employed microfluidic chip technology combined with natural alginate hydrogels to construct 3D liver tissues mimicking hepatic plates. We comprehensively evaluated cultured hepatocyte viability, function, and polarity. Transcriptome sequencing was used to analyze changes in hepatocyte polarity pathways. The data indicate that, as culture duration increases, the viability, function, polarity, mRNA expression, and ultrastructure of the hepatic plate mimetic 3D hepatocytes are enhanced. Furthermore, hepatic plate mimetic 3D cultures can promote changes in the bile secretion pathway via effector mechanisms associated with nuclear receptors, bile uptake, and efflux transporters. This study provides a scientific basis and strong evidence for the physiological structures of bionic livers prepared using 3D cultures. The systems and cultured liver tissues described here may serve as a better in vitro 3D culture platform and basic unit for varied applications, including drug development, hepatocyte polarity research, bioartificial liver bioreactor design, and tissue and organ construction for liver tissue engineering or cholestatic liver injury.